Particulate Matter (PM10, PM2.5, PM1) indoor Pollution by Using Different Fuel Materials - Anh Le, Hoang; Manh Cuong, Dinh; Thi Kim Anh, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 34 No 4DO - 10.25073/2588-1094/vnuees.4284, 2018)
Abstract: Coal, wood, agricultural waste, and liquid petroleum gas (LPG) are among the major fuel materials used for cookstove in Vietnam. However, the use of these energy sources is controversial since they are also the sources of hiden indoor air pollution which could adversely impact human health. In the present study, particulate matter concentrations (PM 10 , PM 2.5 , PM 1 ) are monitored by GRIMM 107-G (Grimm Technologies, Inc., Douglasville, GA, USA) throughout cooking time using different fuels such as coal, wood, and LPG. The results show that the indoor concentrations of particulate matters tend to be higher than those of ambient air. Among the distinguished fuels, wood produces the highest PM 10 , PM 2.5 , PM 1 concentrations, up to 305.7 ± 105.3 µg/m 3 ; 158.3 ± 35.4 µg/m 3 ; 135.9 ± 31 µg/m 3 respectively. The PM 10 indoor and outdoor ratios during cooking time using different fuels such as coal, wood, and LPG are 2.67; 1.18; 0.92 respectively. These high concentration of particulate matters in the kitchen is harmful for people, especially the wives in the household who have longer exposure time to those pollutants. Keywords: Indoor air pollution, cookstove, kitchen room. References [1] N. E. Klepeis, W. C. Nelson, W. R. Ott, J. P. Robinson, A. M. Tsang, S. Paul, J. V. Behar, S. C. Hern, W. H. Engelmann, The National Human Activity Pattern Survey (NHAPS): A resource for assessing exposure to environmental pollutants, Journal of exposure analysis and environmental epidemiology 11 (2001) 231. [2] WHO (2014), 7 million premature deaths annually linked to air pollution; Link: http://www.who.int/mediacentre/news/releases/2014/air-pollution/en/. Last access on 30/07/2018. [3] WHO (2006), Indoor air pollution: 4000 deaths a day must no longer be ignored; Link: http://www.who.int/bulletin/volumes/84/7/editorial30706html/en/. Last access on 30/07/2018. [4] M. S. Crandall, W. K. Sieber, The National Institute for Occupational Safety and Health indoor environmental evaluation experience. Part I: Building environmental evaluations, Applied Occupational and Environmental Hygiene 11 (1996) 533. [5] A. Ellegård, Health effects of cooking air pollution among women using coal briquettes in Hanoi, Environmental technology 18 (1997) 409. [6] N. A. Janssen, P. H. v. Vliet, A. Francée, H. Hendrik, B. Bert, Assessment of exposure to traffic related air pollution of children attending schools near motorways, Atmospheric environment 35 (2001) 3875. [7] S. Lee, M. Chang, Indoor and outdoor air quality investigation at schools in Hong Kong, Chemosphere 41 (2000) 109. [8] H. Richard, E. Richard, H. Tim, School indoor air quality best management practices manual, Washington State Department of Health, Olympia, Washington (1995). [9] J. M. Samet, M. C. Marbury, J. D. Spengler, Health effects and sources of indoor air pollution. Part I, American Review of Respiratory Disease 136 (1987) 1486. [10] K. R. Smith, S. Mehta, The burden of disease from indoor air pollution in developing countries: comparison of estimates, WHO/USAID Global Technical Consultation University of California Berkeley, CA 94720-7360 (2000). [11] K. R. Smith, J. M. Samet, I. Romieu, N. Bruce, Indoor air pollution in developing countries and acute lower respiratory infections in children, Thorax 55 (2000) 518. [12] USEPA, An introduction to indoor air quality (IAQ), United States Environmental Protection Agency (US EPA) (2014) United States. [13] W. Yang, J. Sohn, J. Kim, B. Son, J. Park, Indoor air quality investigation according to age of the school buildings in Korea, Journal of environmental management 90 (2009) 348. [14] Bộ Tài nguyên và Môi trường, Báo cáo hiện trạng môi trường quốc gia năm 2013: Môi trường Không khí, Bộ Tài nguyên và Môi trường, Hà Nội, 2013. [15] Bộ Tài nguyên và Môi trường, Báo cáo hiện trạng môi trường quốc gia giai đoạn 2011 - 2016, Bộ Tài nguyên và Môi trường, Hà Nội, 2016. [16] Quốc hội nước Cộng hòa Xã hội Chủ nghĩa Việt Nam, Luật phòng, chống tác hại của thuốc lá, (2012). [17] T. Beer, T. Grant, G. Morgan, J. Lapszewicz, P. Anyon, J. Edwards, P. Nelson, H. Watson, D. Williams. Comparison of Transport Fuels: Final Report to the Australian Greenhouse Office on the Stage 2 Study of Life-Cycle Emissions - Analysis of Alternative Fuels for Heavy Vehicles. Report No. EV45A/2/F3C, Commonwealth Scientific and Industrial Research Organisation, Aspendale, Victoria, Australia, 2001. [18] B. A. Begum, S. K. Paul, M. D. Hossain, S. K. Biswas, P. K. Hopke, Indoor air pollution from particulate matter emissions in different households in rural areas of Bangladesh, Building and Environment 44 (2009) 898. [19] H. Cachier, C. Liousse, P. Buat-Menard, A. Gaudichet, Particulate content of savanna fire emissions, Journal of Atmospheric Chemistry 22 (1995) 123.